Upaya Membangkitkan Semangat Nasionalisme Anak Melalui Lomba Cerdas Cermat Dalam Rangka Memperingati Hut Ri Ke-78 Di Desa Jineng Kecamatan Wanasaba Kabupaten Lombok Barat - Hani Ardiyantini Hani; Hamzanwadi; Abdul Hanan; Humairo; Firman Ali Rahman (Prodi Tadris IPA Biologi UIN Mataram, 2023)
The character and spirit of nationalism are instinctive and confident embraced by most of the people with whom they build a nation for themselves. As for the alternative to promoting such nationalistic fervor, a clever technique of learning is a technique of learning through a race that can enhance the potential, talent, thinking ability of public knowledge and train of sharp thinking and skillful in answering questions quickly and correctly. This activity is 10 TPQ as participants in the careful intelligent race of two representative groups and each group has three children. The result of this study is the increased nationalism of children reflected in enthusiasm and activity and with a prompt response to questions at the game, the I champion is expected to be by the 800 point TPQ nurul huda at the end of the game, the second most high of the cost of TPQ darul falah by 600, with the third in the third place